Management of pediatric aural foreign bodies: Towards a universal Otolaryngology referral algorithm - Bysice, Andrew; Araslanova, Rakhna; Dzioba, Agnieszka; Husein, Murad (International journal of pediatric otorhinolaryngology, 2023)
Children with aural foreign bodies (AFB) frequently present to the Emergency Department (ED). Our objective was to analyze patterns of pediatric AFB management at our center to characterize children who are commonly referred to Otolaryngology. A retrospective chart review of all children (ages 0–18 years) presenting with AFB to the tertiary care Pediatric ED over a three-year period was performed. Demographics, symptoms, type of AFB, retrieval strategy, complications, need for Otolaryngology referral, and, use of sedation, were evaluated with respect to outcomes. Univariable logistic regression models were conducted to determine which patient characteristics were predictive of AFB removal success. One hundred and fifty-nine patients seen at the Pediatric ED met the inclusion criteria. Average age at presentation was 6 years (2–18 years). Otalgia was the most common presenting symptom (18.0%). However, only 27.0% of children were symptomatic. ED physicians primarily flushed AFBs out of the external auditory canal with water, whereas Otolaryngologists exclusively used direct visualization. Otolaryngology-Head & Neck Surgery (OHNS) was consulted for 29.6% of children. Of these, 68.1% had complications associated with prior retrieval attempts. Sedation was administered in 40.4% of referred children, with 21.2% in an operative setting. Patients experiencing multiple retrieval methods by ED, and, age less than 3 years, were more likely to be referred to OHNS. Patient's age should be strongly considered as a factor for early OHNS referral. By synthesizing our conclusions with previously published results, we propose a referral algorithm.